Awareness and Knowledge of Exercise Physiology Among Syrian Medical Students: A Cross‐Sectional Study. - Khadour, Fater A.; Khadour, Younes A.; Wesley, Hannah (BioMed Research International, 2026)
Background: Exercise physiology is a specialized field of physiology that focuses on examining the effects of exercise and physical activity on the structure and function of living organisms. Knowledge of exercise physiology is essential for enhancing athletic performance, enabling individuals to adapt to extreme conditions, and managing chronic diseases. The objective of this research was to assess the level of knowledge in exercise physiology among medical students in Syria, who are future healthcare professionals. Methods: The data was collected from a cohort of 704 undergraduate medical students who were actively following clinical internships. To evaluate their understanding of exercise physiology, a web‐based survey was utilized as a research tool. The survey is aimed at assessing participants′ foundational knowledge about diverse physiological concepts linked to physical exercise, encompassing topics such as respiratory exchange ratio, physical fitness, V̇O2 max (maximum oxygen uptake), and exercise at high altitudes. Results: A total of 55.5% of the participants exhibited a poor level of knowledge in exercise physiology. Misconceptions were evident regarding various aspects, including the definition (75.7%), application (64.4%), significance (55.3%), and related physiological factors (58.2%) of V̇O2 max. Furthermore, misconceptions were identified in the assessment of physical fitness, with proportions of 51.6%, 42.6%, and 38.8%, respectively, for specific evaluation questions. Similar misconceptions were prevalent in areas such as muscle groups and energy systems during training (34.9%), training prescription variables (42.8%), respiratory exchange ratio (64.4%), and high‐altitude performance (69.9%). Additionally, statistically significant differences in knowledge levels were observed based on respondent characteristics (p < 0.05). Conclusions: Syrian medical students demonstrated limited knowledge and moderate awareness of exercise physiology. These findings emphasize the need to enhance medical curricula by integrating exercise physiology more effectively and promoting active, applied learning strategies to strengthen future physicians′ competence in exercise‐based patient care.